Validation of High Resolution Melting Analysis (HRM) of the Amplified ITS2 Region for the Detection and Identification of Yeasts from Clinical Samples: Comparison with Culture and MALDI-TOF Based Identification - Duyvejonck, Hans; Cools, Piet; Decruyenaere, Johan; Roelens, Kristien; Noens, Lucien; Vermeulen, Stefan; Claeys, Geert; Decat, Ellen; Van Mechelen, Els; Vaneechoutte, Mario (PloS one, 2015)
Candida species are known as opportunistic pathogens, and a possible cause of invasive infections. Because of their species-specific antimycotic resistance patterns, reliable techniques for their detection, quantification and identification are needed. We validated a DNA amplification method for direct detection of Candida spp. from clinical samples, namely the ITS2-High Resolution Melting Analysis (direct method), by comparing it with a culture and MALDI-TOF Mass Spectrometry based method (indirect method) to establish the presence of Candida species in three different types of clinical samples. A total of 347 clinical samples, i.e. throat swabs, rectal swabs and vaginal swabs, were collected from the gynaecology/obstetrics, intensive care and haematology wards at the Ghent University Hospital, Belgium. For the direct method, ITS2-HRM was preceded by NucliSENS easyMAG DNA extraction, directly on the clinical samples. For the indirect method, clinical samples were cultured on Candida ID and individual colonies were identified by MALDI-TOF. For 83.9% of the samples there was complete concordance between both techniques, i.e. the same Candida species were detected in 31.1% of the samples or no Candida species were detected in 52.8% of the samples. In 16.1% of the clinical samples, discrepant results were obtained, of which only 6.01% were considered as major discrepancies. Discrepancies occurred mostly when overall numbers of Candida cells in the samples were low and/or when multiple species were present in the sample. Most of the discrepancies could be decided in the advantage of the direct method. This is due to samples in which no yeast could be cultured whereas low amounts could be detected by the direct method and to samples in which high quantities of Candida robusta according to ITS2-HRM were missed by culture on Candida ID agar. It remains to be decided whether the diagnostic advantages of the direct method compensate for its disadvantages.